Analytical investigation of the role of reinforcement in perpendicular beams of beam-column knee joints by 3D meso-scale model. (1st May 2020) - Eddy, Liyanto; Jiradilok, Punyawut; Matsumoto, Koji; Nagai, Kohei
Highlights: Failures mechanism of RC joints with multidirectional rebars are simulated by meso-scale 3D RBSM. Rebars are meshed into multiple layers to investigate the local bending deformation. Role of rebars in perpendicular beams is successfully revealed using the simulation. Abstract: This paper presents an analytical investigation of the role of the reinforcing bars in the perpendicular beams of beam-column knee joints with mechanical anchorages. A computer simulation using 3D Rigid Body Spring Model (3D RBSM) is used for the analysis of RC beam-column joints in consideration of the effect of multidirectional arrangement of reinforcing steels. Simulation results provide beneficial information for understanding the macroscopic behavior because the internal stresses and crack conditions can be investigated. In this study, the beam-column joint simulation models are varied in the number of reinforcements to study the role of the reinforcing bar in perpendicular beam. Simulation results show that the capacity can be increased when reinforcing bars are added in the perpendicular beams. Through the study of the internal stresses and cracks using numerical simulation, the function of the longitudinal reinforcement in the perpendicular beams is to transfer the stresses from the joint to the perpendicular beams by means of the dowel action which is obtained by utilizing the multiple layers meshing of reinforcement and the local strain distribution. Ultimately, this research also shows that 3D RBSM can be a useful tool for the analysis of the RC beam-column joints with multidirectional arrangement of reinforcing steels based on a case-by case basis that cannot be addressed by the design code and conventional numerical methods.